Relationship of consumer and brand engagement on facebook based on liking behaviour. - Muhammad Al Farhan Md Adnan, (2018)
This research paper is about the factors affecting consumers’ liking behaviour on Facebook brand page. This research focus on the consumer engagement that represent by consumer’s liking brand page. Consumer’s liking brand page is determined by the type of personality traits of consumer. There are three type of personality traits which are extraversion, neuroticism and openness to experiences involve in this research and one factor as mediating factor which is broadcasting mode of interaction. These factors contribute to the level of consumer engagement which is liking behaviour. From data analysis, researcher found that one of the factor contribute more to the level on consumer engagement and the presence of mediating factor increase more the level of consumer engagement. This research can help the brand manager to identify the type of consumer that contributes to the level of liking behaviour. By identifying these factor, brand manager can attract more people based on the personality traits.